2012
DOI: 10.1111/j.1469-8749.2012.04312.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐relationships of functional status in cerebral palsy: analyzing gross motor function, manual ability, and communication function classification systems in children

Abstract: AIM To investigate the relationships among the Gross Motor Function Classification System (GMFCS), Manual Ability Classification System (MACS), and Communication Function Classification System (CFCS) in children with cerebral palsy (CP). METHOD Using questionnaires describing each scale, mothers reported GMFCS, MACS, and CFCS levels in 222 children with CP aged from 2 to17 years (94 females, 128 males). Children were referred from pediatric developmental/behavioral, physiatry, and child neurology clinics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
92
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 22 publications
13
92
2
6
Order By: Relevance
“…In line with others, 8 a moderate correlation was found between the CFCS and GMFCS levels, thereby emphasizing the association between severity of CP (expressed in GMFCS levels) and disabilities in expressive and receptive communication. 22 No significant correlation was found between type of CP and CFCS levels, suggesting that communication problems occur within every type of CP.…”
Section: Discussion Cfcs-nlsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with others, 8 a moderate correlation was found between the CFCS and GMFCS levels, thereby emphasizing the association between severity of CP (expressed in GMFCS levels) and disabilities in expressive and receptive communication. 22 No significant correlation was found between type of CP and CFCS levels, suggesting that communication problems occur within every type of CP.…”
Section: Discussion Cfcs-nlsupporting
confidence: 90%
“…3,5,6 Because the diagnosis of CP is based on clinical features but does not describe all the consequences of the disability, 7 the diagnosis must be used in combination with functional classifications. [8][9][10] Using a five-level approach, the Communication Function Classification System (CFCS) can classify the everyday communication of a person with CP, including communication with AAC systems. 11 Distinctions between the five levels of the CFCS are based on important aspects of functional communication, namely the performance of the sender and receiver roles, the pace of the conversation, and the type of communication partner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study from Hidecker et al presents the results for three scales: the Gross Motor Function Classification System (GMFCS), the Manual Ability Classification System (MACS), and the Communication Function Classification System (CFCS). 2 A clinical series of 222 children with CP were assessed, half of whom were born very preterm. Examples of the advantages of knowing each child's functional profile are given, as well as excellent demonstrations of how awareness of these children's needs might be increased and care improved when using information from these three scales.…”
mentioning
confidence: 99%
“…In some studies, significant moderate to high correlation was found, another study presented nonsignificant correlation. 3,[5][6][7] Thus, the aim of this study was to discover the correlation between GMFCS and CFCS with sample taken from Dr. Hasan Sadikin General Hospital (RSHS) Bandung, a tertiary health care facility with a high number of children with CP…”
Section: Introductionmentioning
confidence: 99%